Econometrics analysis of the impact of external shocks on foreign direct investment in Iraq for the period (1995-2016) - فخري سامر محمد (Journal of Economics and Administrative Sciences, 2018)
The external shocks are one of the phenomena that the Iraqi economy is exposed to over a period of time. It is referred to as changes and events that come from outside the economic system and extends to many economic variables. However, foreign direct investment may be severely affected due to the extreme sensitivity to changes and local and international developments. This type of trauma and its characteristics to help manage and cope with external shocks, and in order to avoid the standard problems experienced by some models of simple linear regression, multi-linear regression models were used with variables Scientific and other dummy variables . The study found that the external shocks in Iraq have positive effects such as the changes of economic globalization and the increase in international oil prices on the flow of foreign direct investment and negative ones such as wars and armed conflicts. The research presented some proposals, including the creation of specialized scientific centers using modern standard methods to deal with the potential negative effects of external shocks.